The Role of Responsible Management in Job Satisfaction and Performance Within Banking Firms (Journal of Business, Universidad del Pacífico (Lima, Peru), 2020)
In recent years the need for responsible management of financial institutions, in terms of organizational commitment to supporting society and strategies for sustainable economic development, has become increasingly pressing. The aim of this article is to determine the influence that management has on job satisfaction and performance at banking firms based in northeast Mexico. The primary data were obtained using an instrument applied to management-level employees of public and private banking firms in the cities of Ensenada and Tijuana in Baja California; and Hermosillo, Guaymas, Ciudad Obregón, and Navojoa in Sonora.  The statistical technique of linear regression modeling was used to analyze and validate the results, with the aid of the Statistical Package for the Social Sciences (SPSS), version 25. The results show that managerial commitment is a key factor in the organizational performance of responsible banking. Thus, the greater the management responsibility for socially responsible actions, the stronger the positive influence on employees’ job satisfaction in the sector. It was also found that the banks are generally well predisposed to corporate social responsibility, and that commitment has a positive and significant relationship with the performance of these institutions.
Keywords: Management; job satisfaction; social responsibility; organizational commitment; performance